Semisynthesis of horse heart cytochrome c analogues from two or three fragments. - ten Kortenaar, P B (1985)
Horse heart cytochrome c was cleaved with cyanogen bromide. The largest fragment, [Hse65]cytochrome c-(1-65)-pentahexacontapeptide lactone, was used in condensations involving four analogues of the complementary cytochrome c-(66-104)-nonatriacontapeptide. Two of the latter compounds were obtained from a semisynthesis starting with a partially protected fragment N epsilon 86-88,99,100-penta(methylsulfonylethyloxycarbonyl)cytochrome c-(81-104)-tetracosapeptide (also arising from a cyanogen bromide-mediated degradation) and analogues of the middle part, cytochrome c-(66-80)-pentadecapeptide, which were prepared by organochemical synthesis. Two other analogues of the cytochrome c-(66-104)-nonatriacontapeptide were prepared entirely by organochemical synthesis. Each of the covalently recombined analogous cytochromes c could retain an electron in the presence of oxygen and transfer it to cytochrome c oxidase, although with different reaction rates and Michaelis constants. Their redox potentials varied over a broad range. The exchanges Tyr67----Phe(F) and Thr78----Val gave rise to analogues with a lower redox potential than native cytochrome c, while the exchange Phe82----Leu or Tyr97----Leu led to analogues with the same and a higher redox potential, respectively.